2021
DOI: 10.1111/febs.16123
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of the influenza A virus polymerase subunit PA in the N‐terminal domain positively regulates its endonuclease activity

Abstract: The post-translational acetylation of lysine residues is found in many nonhistone proteins and is involved in a wide range of biological processes. Recently, we showed that the nucleoprotein of the influenza A virus is acetylated by histone acetyltransferases (HATs), a phenomenon that affects viral transcription. Here, we report that the PA subunit of influenza A virus RNA-dependent RNA polymerase is acetylated by the HATs, P300/ CREB-binding protein-associated factor (PCAF), and general control nonderepressib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Above acetyltransferases and deacetylases exert their proviral and antiviral function, respectively, during IAV infection through both viral and host effectors. The acetyltransferases, Gcn5 and PCAF are involved in the suppression of the expression of host type I IFN and ISGs such as STAT1, MX1 and viperin ( 15 ), p300/CBP are implicated in the regulation, both positive and negative, of the expression of multiple host proteins involved in various stages of IAV life cycle ( 29 ), whereas NAA20/25 and also Gcn5 and PCAF facilitate the positive regulation of the IAV polymerase and host shutoff activities through acetylation of viral proteins ( 16 , 31 , 32 ). In contrast, HDAC6 ( 14 ) and HDAC11 ( 13 ) are involved in the enhancement of the IAV-induced type I IFN production.…”
Section: Discussionmentioning
confidence: 99%
“…Above acetyltransferases and deacetylases exert their proviral and antiviral function, respectively, during IAV infection through both viral and host effectors. The acetyltransferases, Gcn5 and PCAF are involved in the suppression of the expression of host type I IFN and ISGs such as STAT1, MX1 and viperin ( 15 ), p300/CBP are implicated in the regulation, both positive and negative, of the expression of multiple host proteins involved in various stages of IAV life cycle ( 29 ), whereas NAA20/25 and also Gcn5 and PCAF facilitate the positive regulation of the IAV polymerase and host shutoff activities through acetylation of viral proteins ( 16 , 31 , 32 ). In contrast, HDAC6 ( 14 ) and HDAC11 ( 13 ) are involved in the enhancement of the IAV-induced type I IFN production.…”
Section: Discussionmentioning
confidence: 99%
“…The partial recombinant protein of the LymCBP HAT domain (from 1240th arginine to 1641st lysine, GenBank accession number BAE02656.1) with His 6 -tag was synthesized in Escherichia coli and purified as previously described, with slight modifications. [36][37][38] LymCBP catalytic domain was amplified by RT-PCR with cDNA prepared from Lymnaea CNSs, PrimeSTAR® HS DNA Polymerase (Takara Clontech), and primers, whose nucleotide sequences were summarized in Table S1 (No. 23,24).…”
Section: Recombinant Protein Of Lymcbpmentioning
confidence: 99%
“…Interestingly, viral polymerase activity increases after silencing PCAF and decreases after silencing GCN5, suggesting that the acetylation of K31 and K90 has opposite effects on viral replication [ 61 ]. Hatakeyama et al also verified that PCAF and GCN5 can acetylate K19 on the PA subunit of the IAV RNA-dependent RNA polymerase, enhancing its endonuclease and RNA-dependent RNA polymerase activity while also affecting viral transcription [ 64 ]. Ma et al reported that the acetylation of K77, K113, and K229 on NP and of K108 on NS1 of IAV enhances the activity of these proteins and induces IFN antagonism, which promotes viral replication and survival [ 62 , 63 ].…”
Section: Acetylation Of Viral Proteinsmentioning
confidence: 99%